GAMBARAN MINAT KEWIRAUSAHAAN MAHASISWA - Yanti Pujiastuti; Eldes Willy Filantrovi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This study aims to find out the description of students' entreprenership interests and the factors that influence them. Factors studied are motivation, education and family environment. The study was conducted on STIE Bank BPD Central Java students who have taken entrepreneurship courses. Sampling using purposive sampling and obtained 90 samples. Data collected through questionnaires were analyzed using regression techniques. The test results found that partially the entrepreneurship motivation and entrepreneurship education had a positive and significant effect on entrepreneurial intention. Simultaneous testing shows that entrepreneurship motivation, entrepreneurial education and family environment together have a significant effect on entrepreneurial intention. Efforts to increase entrepreneurship intention can be done by increasing entrepreneurship motivation and entrepreneurship education.